Comparative Study of Separation Techniques for Multi-Component Organic-Inorganic Mixtures Using Extraction, Distillation, and Evaporation - Dokduea, Jidapha; Meetpetchdee, Yanika; Somboonchai, Jidapha (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2025)
The separation and purification of chemical compounds from multi-component mixtures is a fundamental process in chemistry and pharmaceutical sciences. This study evaluated the effectiveness of liquid-liquid extraction, simple distillation, evaporation, recrystallization, and acid-base extraction techniques for separating four different ternary mixtures: (i) chloroform, methanol, and sodium acetate; (ii) salicylic acid, diethyl ether, and sodium chloride; (iii) benzoic acid, distilled water, and diethyl ether; and (iv) salicylic acid, ethanol, and distilled water. Each mixture was systematically separated using appropriate techniques based on differences in polarity, boiling point, and solubility. The results demonstrated that the percent error values varied considerably across different compounds and methods, ranging from 2.30% to 93.60%. Recrystallization and distillation showed higher accuracy for non-volatile solids and low-boiling-point liquids, respectively, while liquid-liquid extraction efficiency was influenced by polarity differences and procedural factors. These findings provide a comprehensive comparison of classical separation techniques applicable to pharmaceutical and chemical laboratory practice.